An Applied Computable Equilibrium (ACE) model of the CAP cereal policy reforms: the case of Ireland - Boyle, G. E. (Economic & Social Studies, 1995)
In this paper an Applied Computable Equilibrium (ACE) model is constructed to examine the economic impact of the CAP (Mac Sharry) cereal policy reforms. The model is applied to Irish data. The reforms comprise three elements: (i) a 29 per cent reduction in "support" prices; (ii) a requirement that producers "set aside" 15 per cent of the land devoted to cereal production, and (iii) compensation for the price reduction and "set aside". The simulations for Ireland suggest that production of cereals could fall by between 14 per cent and 9 per cent. The usage of intermediate inputs (mainly fertilisers) could fall by between 19 per cent and 9 per cent. The outcome for land values is dependent, inter alia, on the assumed technology of the production system.
Keywords: Applied Computable Equilibrium; Common Agricultural Policy; Ireland; Cereal policy